Usability testing analysis of the Lhokseumawe district attorney’s office website using nielsen’s metrics for user experience evaluation - Alfarisyi, Ahmad; Sahputra, Ilham; Eviyanti, Cut Yuniza; Karima, Annisa (Geuthèë Institute, 2025)
The Lhokseumawe district attorney's office is a law enforcement institution that utilizes a website as an essential medium for delivering public information and services. To ensure its optimal function, this research aims to evaluate the website's usability quality level. This study adopts the Usability Testing method with a quantitative descriptive approach , based on the five metrics proposed by Jakob Nielsen: learnability, efficiency, memorability, errors, and user satisfaction. Data collection involved direct observation of 10 users performing core task scenarios, supplemented by questionnaires and interviews. The test results indicate that the website generally meets several usability aspects. However, there are still significant shortcomings in the areas of efficiency and user satisfaction. Quantitatively, the website's total usability score is 87.5% , with the average satisfaction score using the System Usability Scale (SUS) being 65%. Based on these findings, this study recommends improvements to the navigation structure and user interface (UI) design to enhance the quality of digital services and provide a better user experience (UX). The results of this study are expected to serve as a reference for the website administrators of the Lhokseumawe District Attorney's Office for further system development